Efficacy of Postoperative Oral Antibiotics in Foot and Ankle Surgery. (September 2022) - Frederick, Robert M.; Burnette, Hannah; Joyce, Myles; Kumar, Padam; McGee, Trevor; Chiu, Chi-Yang; Bettin, Clayton C.; Grear, Benjamin J.; Murphy, G. Andrew; Richardson, David R.
Background: Preoperative oral antibiotic use in patients undergoing foot and ankle surgery is standard practice, but no consensus has been reached regarding the efficacy of postoperative oral antibiotics. The purpose of this study was to determine whether postoperative oral antibiotics reduce the rate of surgical site infections (SSIs) in patients, with and without comorbidities, undergoing foot and ankle surgery. Methods: A retrospective chart review was conducted identifying patients who underwent foot and ankle surgery by 4 fellowship-trained, foot and ankle orthopaedic surgeons between January 1, 2015, and January 1, 2019. Patients were divided into 2 groups: those who received postoperative oral antibiotics (group 1) and those who did not (group 2). Two surgeons routinely prescribed postoperative oral antibiotics, and 2 did not. Demographics, comorbidities, and procedure complexity based on surgical site and Current Procedural Terminology code were recorded from the charts. The primary outcome was postoperative infection (superficial or deep) within 6 months after surgery. Patients with antibiotic use prior to surgery, preoperative infection, or lack of follow-up >6 weeks were excluded. Multivariate logistic regression modeling was used to analyze differences in infection rate and severity. Results: Chart review identified 3631 patients, 1227 of whom did not receive postoperative oral antibiotics whereas 2394 patients did. Routine postoperative oral antibiotic use did not significantly affect postoperative infection rates or severity. However, all covariates studied (diabetes, hypertension, obesity, tobacco use, alcohol use, rheumatoid conditions, and age) influenced postoperative infection rates and severity. Conclusion: The results of this study indicate that postoperative oral antibiotics are not associated with differences in infection rates or severity. We do not recommend routine use in foot and ankle surgery.